Abgestorben?: Religionsrecht der DDR und der Volksrepublik Polen - Vogel, Viola (Jus Ecclesiasticum, 2015)
Lenin and Stalin corrupted Marx vision of the death of religion in a future society and combined the theory of Marxism-Leninism with atheism and the fight against churches in the former Soviet Union as well as in other socialist countries. Viola Vogel examines the philosophical background of the religious criticism of Marx and Lenin and describes the interactions and repercussions of the legal and state concept of the GDR and the Peoples Republic of Poland with regard to the socialist religious laws and the religious main groups in both countries.